Spatial point pattern analysis of the Sumatran tiger (Panthera tigris sumatrae) poaching cases in and around Kerinci Seblat National Park, Sumatra - FARID RIFAIE; JITO SUGARDJITO; YULI SULISTYA FITRIANA (Biodiversitas Journal of Biological Diversity, 2015)
Rifaie F, Sugardjito J, Fitriana YS. 2015.Spatial point pattern analysis of the Sumatran tiger (Panthera tigris sumatrae)poaching cases in and around Kerinci Seblat National Park, Sumatra. Biodiversitas 16: 311-319.Wild Sumatran tigers are in a criticalstate with around 250 adult tigers remain in their habitat in Sumatra Island. Despite the fact that this subspecies is an elusive animal withvery wide home range, Sumatran tigers are facing two serious threats, the depletion of its habitats and preys in one side and the increaseof tiger hunt for illegal wildlife market. Improving the capacity and effectiveness of law enforcement in reducing poaching of tigers isan immediate priority protecting the remaining wild populations in their habitat. Enforcement monitoring was established under theTiger conservation program. During their patrols, the anti-poaching team recorded various data including poaching incidents. Weanalyzed secondary data of Sumatran tiger poaching cases around Kerinci Seblat National Park that have been documented from 2000 to2012. Georeferencing process was performed to transform locality data of 87 poaching cases into geographic position. The NearestNeighbor (NN) analysis suggested a strong clustering pattern with the observed mean distance was 4.9 km, much lower than theexpected mean distance (10.9 km).Similarly, The Ripley's K analysis also showed the aggregation of the points along the observeddistances. On the other hand, about 35.6% of points were located outside the standard deviational ellipse. The pattern indicated thatpoaching incidents were spread in all corner of the region but excessive cases were observed in the center of the park.